THE ROLE OF KOMILJON OTANIYAZOV IN THE DEVELOPMENT OF UZBEK ART (Archive of Conferences, 2021)
Folk art is a huge ocean. It is constantly enriched with the products of the creative people and is constantly growing. After all, each sample that is part of this ocean is explained by its own secrets, irrigated by national traditions, national psyche and national values. This is the main basis for the formation and development of Uzbek national music and literature.This article discusses the role of Komiljon Otaniyazov in the development of Uzbek art.